Long-Term Narrowband Lighting Influences Activity but Not Intrinsically Photosensitive Retinal Ganglion Cell-Driven Pupil Responses - Lou, Linjiang; Arumugam, Baskar; Hung, Li-Fang; She, Zhihui; Beach, Krista M.; Smith, Earl L.; Ostrin, Lisa A. (Frontiers in Physiology, 2021)
Purpose: Light affects a variety of non-image forming processes, such as circadian rhythm entrainment and the pupillary light reflex, which are mediated by intrinsically photosensitive retinal ganglion cells (ipRGCs). The purpose of this study was to assess the effects of long- and short-wavelength ambient lighting on activity patterns and pupil responses in rhesus monkeys. Methods: Infant rhesus monkeys were reared under either broadband “white” light (n=14), long-wavelength “red” light (n=20; 630 nm), or short-wavelength “blue” light (n=21; 465 nm) on a 12-hour light/dark cycle starting at 24.1 ± 2.6 days of age. Activity was measured for the first 4 months of the experimental period using a Fitbit activity tracking device and quantified as average step counts during the daytime (lights-on) and nighttime (lights-off) periods. Pupil responses to 1 second (s) red (651 nm) and blue (456 nm) stimuli were measured after approximately 8 months. Pupil metrics included maximum constriction and the 6 s post-illumination pupil response (PIPR). Results: Activity during the lights-on period increased with age during the first 10 weeks (P < 0.001 for all), and was not significantly different for monkeys reared in white, red, or blue light (P = 0.07). Activity during the 12-hour lights-off period was significantly greater for monkeys reared in blue light compared to those in white light (P = 0.02), but not compared to those in red light (P = 0.08). However, blue light reared monkeys exhibited significantly lower activity compared to both white and red light reared monkeys during the first hour of the lights-off period (P = 0.01 for both) and greater activity during the final hour of the lights-off period (P < 0.001 for both). Maximum pupil constriction and the 6 s PIPR to 1 s red and blue stimuli were not significantly different between groups (P > 0.05 for all). Conclusions: Findings suggest that long-term exposure to 12-hour narrowband blue light results in greater disruption in nighttime behavioral patterns compared to narrowband red light. Normal pupil responses measured later in the rearing period suggests that ipRGCs adapt after long-term exposure to narrowband lighting.